EVALUASI OVERALL EQUIPMENT EFFECTIVENESS SEBAGAI UPAYA PERBAIKAN PRODUKTIVITAS MESIN PRODUKSI KAIN NON-WOVENS (STUDI KASUS PT. MEGAH SEMBADA INDUSTRIES) - Hartono, Hartono; Putra, Aldi Pramana; Suryatman, Tina Hernawati (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2020)
The manufacturing industry has a system for applying machinery, labor, equipment and raw materials to be transformed into a product that has a sale value. Production machinery and equipment are the main resources that cannot be separated from the overall resource system owned by the company. At PT. Sumber Wovens Utama production machines are used nonstop and cause a decrease in performance of these machines which include frequent breakdowns, loss of ideal speed, and poor quality. The purpose of this study is to determine the overall value of the effectiveness of the production machinery at this time, to find the root cause of the overall equipment effectiveness value is not as expected, and to provide an improvement to the cause of the low value of the overall equipment effectiveness of the non-wovens fabric production machine. The method used in this research is the Overall Equipment Effectiveness Method to calculate the level of effectiveness and productivity of production machines, Fishbone Diagrams to solve problems in projects and Analysis of 5 why to provide improvements to the level of productivity of these machines. The results showed that the average overall equipment effectiveness value for the period November 2018 - April 2019 was 83.2%, this value was still below the world class standard of 85%. Therefore, it is given an improvement over the overall equipment effectiveness value not being achieved by making regular maintenance schedules for production machines, making standard product changeover procedures, making standard parameters for each type of product and updating it every 1 month, etc. so that it gets good results, namely increases the overall equipment effectiveness value of the production machine to be 88.30%.Keywords: Overall Equipment Effectiveness, Fishbone Diagram, 5 why analys, Mesin Produksi, Kain Non-wovens, Production Machine, Non-wovens Fabric